“Riesgos ergonómicos y enfermedades profesionales en los trabajadores del área de catering de la empresa MISHAN SERVICES S.A. de la provincia de Pichincha. Diseño de una propuesta de intervención de un sistema de control de riesgos ergonómicos mediante la aplicación de un programa de salud ocupacional” - Sánchez Chacán, Sofía Paola (2015)
In the present research work, a study of the ergonomic risk was developed in the tasks of each of the jobs that the production process of the catering area has and the analysis of possible occupational diseases in the company MISHAN SERVICES S.A., the same one that is dedicated to the provision of complementary food and cleaning services for the oil sector. Its offices are located in the Parish of Carcelén, Canton Quito, Province of Pichincha, and its service processes are located in the provinces de Orellana, and Sucumbíos, with its main clients being companies in the Oil sector such as HERMERICH & PAYNE, NABORS, TUSCANY, SINOPEC, SWANBERG, HILONG, and the State Operator PETROAMAZONAS E.P.